A highly stable non-noble metal Ni2P co-catalyst for increased H2 generation by g-C3N4 under visible light irradiation. Issue 18 (20th April 2017) - Ye, Ping; Liu, Xinling; Iocozzia, James; Yuan, Yupeng; Gu, Lina; Xu, Gengsheng; Lin, Zhiqun
Abstract : Ni2 P serves as a highly stable non-noble-metal co-catalyst to efficiently promote H2 generation of g-C3 N4 . Abstract : Nickel phosphide (Ni2 P) was grown on a graphitic carbon nitride (g-C3 N4 ) surface by annealing a mixture of g-C3 N4, NiCl2, and NaH2 PO2 at 400 °C for 2 h in an Ar atmosphere. During the annealing, Ni2 P particles formed intimate interfaces with g-C3 N4 . As a result, charge transfer from photo-excited g-C3 N4 to Ni2 P was improved as demonstrated by the improved photocatalytic H2 generation (40.5 μmol h −1 g −1 ) compared to a physical mixture of Ni2 P and g-C3 N4 (trace H2 generation). Under optimal and identical experimental conditions, the H2 production rate on Ni2 P-loaded g-C3 N4 (2 wt%) is 82.5 μmol h −1 g −1, which is higher than that of Pt-loaded g-C3 N4 (0.5 wt%) (72 μmol h −1 g −1 ). Impressively, Ni2 P shows a highly stable H2 production activity despite being a non-noble metal co-catalyst. No activity loss occurs over repeated use and 24 h long-term H2 generation trials. In contrast, a pronounced reduction in H2 generation was observed for Pt-loaded g-C3 N4 (0.5 wt%) over the same 24 hour trial period. Among their many advantages, including non-toxicity, low cost and natural abundance, Ni2 P/g-C3 N4 composites are a promising alternative for realizing efficient, long-lasting photocatalytic H2 production.